Lifetime and Jail-Specific Suicidal Ideation: Prevalence and Correlates in a Sample of People in Jail in the United States - Stoliker, Bryce E. (International journal of offender therapy and comparative criminology, 2025)
Despite high suicide mortality in U.S. jails, there is limited research into precursors for suicide in this population, such as suicidal ideation. The current study examined the prevalence and correlates of lifetime and jail-specific suicidal ideation among a sample of 196 individuals (137 men) in custody in a U.S. jail. Nearly half the sample had reported lifetime suicidal ideation (45%), whereas 30% had reported jail-specific suicidal ideation. Adjusted correlates of lifetime suicidal ideation included a history of mental illness (OR = 2.79) and drug use (OR = 2.70). Adjusted correlates of jail-specific suicidal ideation included a history of mental illness (OR = 2.74), drug use (OR = 3.16), and a dehumanizing custodial environment (OR = 3.74). Some theoretically and empirically relevant factors were not significantly associated with suicidal ideation. Both expected and unexpected findings are discussed within the context of suicide theory and research, and practical implications are explored.